2023
DOI: 10.1002/admi.202300014
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of K‐Intercalated Epitaxial Bilayer Graphene

Abstract: In particular, graphene-based materials attracted considerable scientific interest due to the recent discovery of superconductivity in twisted bilayer graphene. [3][4][5] Superconductivity has also been observed in layered, graphene-based systems upon chemical doping via metal intercalation, with transition temperatures up to 11.5 K for calcium-intercalated bulk graphite. [6,7] However, for metal-intercalated, graphenebased systems the reported critical temperatures strongly depend on i) the choice of the atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20] For the fabrication of 2D superconducting graphene, the process involves the deposition of alkali metal or alkaline-earth metal onto monolayer graphene, as well as the intercalation of alkali metal atoms into bilayer graphene. 21 For example, superconductivity has been first detected in alkali metal deposited graphene KC 8 with T c of 0.55 K. 22 Moreover, alkaline-earth metal Ca-deposited graphene CaC 6 and alkali metal Li-deposited graphene LiC 6 were theoretically predicted to be phonon-mediated superconductors with superconducting T c of 1.4 and 8.1 K, 23 respectively. Moreover, after applying 10% biaxial tensile strain, it was predicted that the T c of LiC 6 increases from 8.1 K to about 28.7 K. 24 Subsequent experiments have confirmed the superconductivity of LiC 6 at a temperature of 5.9 K. 25 It has been predicted that metals-deposited graphene, such as AlC 8 , could exhibit superconductivity with T c exceeding 22 K at the experimentally accessible hole doping and tensile strain levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19][20] For the fabrication of 2D superconducting graphene, the process involves the deposition of alkali metal or alkaline-earth metal onto monolayer graphene, as well as the intercalation of alkali metal atoms into bilayer graphene. 21 For example, superconductivity has been first detected in alkali metal deposited graphene KC 8 with T c of 0.55 K. 22 Moreover, alkaline-earth metal Ca-deposited graphene CaC 6 and alkali metal Li-deposited graphene LiC 6 were theoretically predicted to be phonon-mediated superconductors with superconducting T c of 1.4 and 8.1 K, 23 respectively. Moreover, after applying 10% biaxial tensile strain, it was predicted that the T c of LiC 6 increases from 8.1 K to about 28.7 K. 24 Subsequent experiments have confirmed the superconductivity of LiC 6 at a temperature of 5.9 K. 25 It has been predicted that metals-deposited graphene, such as AlC 8 , could exhibit superconductivity with T c exceeding 22 K at the experimentally accessible hole doping and tensile strain levels.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent theoretical calculations have revealed that C 6 CaC 6 possesses the capability to sustain phonon-mediated superconductivity, with a T c ranging from 6.8 to 8.1 K. 28 Recently, a research group successfully introduced Ca atoms into the top bilayer of a trilayer graphene film on the SiC substrate to form C 6 CaC 6 , and observed T c of 8.83 K. 29 The above experimental results 27,29 agree excellently with the theoretical results. Nowadays, an experimental study has successfully prepared K-intercalated bilayer graphene, and the resulting T c was determined to be 3.6 K. 21 However, the T c of them are comparatively low. The open question in the current study is whether the T c of bilayer graphene superconductors can be increased.…”
Section: Introductionmentioning
confidence: 99%
“…It can conduct thermal and electrical conductivity even higher than copper. Since it has a high ability to conduct thermal conductivity, it will reduce the battery's temperature by dissipating the resulting heat, thus increasing the battery's efficiency and allowing it to be used at high temperatures [17]. It also has a high degree of strength and flexibility in addition to its low weight, which is about 5 times less than the weight of aluminum.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Graphene-based superconductors are promising for diverse applications owing to their optical transparency, mechanical strength, and flexibility. Among these materials, C 6 CaC 6 , a bilayer graphene intercalated with calcium, exhibits the highest critical temperature ( T c ). It was synthesized via molecular beam epitaxy (MBE) in an ultrahigh vacuum from trilayer, bilayer, , and monolayer graphene.…”
mentioning
confidence: 99%